Assessing the impact of climate change on Euphrates and Tigris discharge using distributed hydrologic model - Salkım, Emre (Graduate School, 2024)
Hosting Türkiye, Syria, Iraq, and Iran, Euphrates-Tigris Basin is a significant case facing the earliest consequences of climate change. Considering its semi-arid nature and lack of hydro-political governance among its riparians, consistency of hydroclimatic research over the region is vital. Accordingly, in the first part of this research, historical and future simulations of three regional climate models (RCMs) (CLMcom-KIT-CCLM5-0-15, GERICS-REMO2015, and ICTP-RegCM4-7) dynamically downscaled from three earth surface models (ESMs) (HadGEM2, MPI-ESM, and NorESM1) (total of nine) by Coordinated Regional Climate Downscaling Experiment's Africa domain (CORDEX- Africa) were evaluated over the Euphrates and Tigris Basin (ETB). Biases of these RCMs were showcased by comparing the reference period to the corresponding ERA5 reanalysis, considering the mean daily surface temperature at 2 meters (°C) and daily total precipitation (mm/day). Distinctions emerge in the analysis of bias maps. Seasonal analysis of the RCMs during the reference period further exhibits these distinctions. Multi- model ensembles (MME) were created to increase the certainty of future predictions regarding RCP2.6 and RCP8.5. MMEs outperform each RCM in terms of hindcasting. To overcome remaining systematic biases and preserve the extremes for future periods, bias corrections were carried out using empirical quantile mapping. Corrected data indicate increased temperatures for ETB regarding both scenarios by the end of the century (up to 1.5°C for RCP2.6 and 5.7°C for RCP8.5). Since ETB is a semi-arid region, changes in precipitation and potential evapotranspiration over the basin were not remarkable reaching up to 0.1 mm/day increase for RCP 2.6 and RCP8.5. The resulting data presents the changes in the basin's climate in the 21st century, provide a comprehensive retrospective benchmarking opportunity for the developing datasets in the CORDEX family (e.g., CMIP6), and offer strategic insight regarding in-situ data scarcity over the region. During the second part of this research, obtained MME data were used to run The Mesoscale Hydrologic Model (mHM) to investigate the changes in routed streamflow, total surface runoff and the depth of snowpack within ETB. The outputs of mHM show up to 15% increase for Euphrates and up to 10% decrease for Tigris River systems in terms of routed streamflow by the end of the century regarding RCP2.6. RCP8.5 showcases more drastic changes reaching up to 25% decrease in the discharge levels for the last period of this investigation. Up to 25% increase is expected on the southeastern parts of the basin as the amount of increasing precipitation also supports this outcome. Decrease in the depth of snowpack and the apparent shift in snowmelt is remarkable over the mountainous areas which needs further investigation. Overall, ETB is likely to face substantial changes in the near and the distant future, as these changes put the water, food, and energy nexus in danger, threatening the ETB's prosperity and sustainable development.
İklim değişikliğinin Fırat ve Dicle nehir akımları üzerindeki etkisinin dağılı hidrolojik modelle değerlendirilmesi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2024
Keywords: Basin modelling; Havza modellemesi; Hydrological modelling; Hidrolojik modelleme; Hydrometeorology; Hidrometeoroloji